Thrombosis of the Abdominal Veins in Childhood - Kumar, Riten; Kerlin, Bryce A. (Frontiers in Pediatrics, 2017)
Abdominal venous thrombosis is a rare form of venous thromboembolic disease in children. While mortality rates are low, a significant proportion of affected children may suffer long-term morbidity. Additionally, given the infrequency of these thrombi, there is lack of stringent research data and evidence-based treatment guidelines. Nonetheless, pediatric hematologists and other subspecialists are likely to encounter these problems in practice. This review is therefore intended to provide a useful guide on the clinical diagnosis and management of children with these rare forms of venous thromboembolic disease. Herein, we will thus appraise the current knowledge regarding major forms of abdominal venous thrombosis in children. The discussion will focus on the epidemiology, presentation, diagnosis, management, and outcomes of (1) inferior vena cava, (2) portal, (3) mesenteric, (4) hepatic, and (5) renal vein thrombosis.